Complementary and alternative medicine treatments for common skin diseases: A systematic review and meta-analysisCapsule Summary - Virginia A. Jones, MD, MS; Payal M. Patel, MD; Claire Wilson, BS; Hongnan Wang, MS; Kurt A. Ashack, MD, MHS (Elsevier, 2021)
Background: Complementary and alternative medicine (CAM) treatments are growing in popularity as alternative treatments for common skin conditions. Objectives: To perform a systematic review and meta-analysis to determine the tolerability and treatment response to CAM treatments in acne, atopic dermatitis (AD), and psoriasis. Methods: PubMed/Medline and Embase databases were searched to identify eligible studies measuring the effects of CAM in acne, AD, and psoriasis. Effect size with 95% confidence interval (CI) was estimated using the random-effect model. Results: The search yielded 417 articles; 40 studies met the inclusion criteria. The quantitative results of CAM treatment showed a standard mean difference (SMD) of 3.78 (95% CI [−0.01, 7.57]) and 0.58 (95% CI [−6.99, 8.15]) in the acne total lesion count, a SMD of −0.70 (95% CI [−1.19, −0.21]) in the eczema area and severity index score and a SMD of 0.94 (95% CI [−0.83, 2.71]) in the scoring of atopic dermatitis score for AD, and a SMD of 3.04 (95% CI [−0.35, 6.43]) and 5.16 (95% CI [−0.52, 10.85]) in the Psoriasis Area Severity Index score for psoriasis. Limitations: Differences between the study designs, sample sizes, outcome measures, and treatment durations limit the generalizability of data. Conclusions: Based on our quantitative findings we conclude that there is insufficient evidence to support the efficacy and the recommendation of CAM for acne, AD, and psoriasis.